Fine‐tuning light sensitivity in the starry flounder (Platichthys stellatus) retina: Regional variation in photoreceptor cell morphology and opsin gene expression. Issue 10 (21st April 2017) - Iwanicki, Tom W.; Novales Flamarique, Iñigo; Ausiό, Juan; Morris, Emily; Taylor, John S.
Abstract: Vertebrate color vision relies on the differential expression of visual pigment proteins (opsins) in cone photoreceptors of the retina. The diversity of opsins and their retinal expression patterns appear greatest for animals that experience variable light habitats, as is the case with flatfishes. Yet, opsin repertoires and expression patterns in this group of fishes are poorly described. Here, we unveil the visual opsin expression patterns of juvenile starry flounder ( Platichthys stellatus ) and describe the localization of cone types, their visual pigments and opsin expression. Juvenile starry flounder express eight opsins ( Rh1, Sws1, Sws2A1, Sws2A2, Sws2B, Rh2A1, Rh2A2, Lws) and possess a corresponding number of photoreceptor visual pigments, with peak absorbance ranging from 369 to 557 nm. Retinal (vitamin A1) was the only chromophore detected in the retina. Intraretinal variation in opsin abundance consisted of greater expression of both RH2, and lesser expression of SWS1 and both SWS2A, opsin transcripts in the dorsal compared to the ventral retina. Overall cone density was greater in the dorsal retina which was also characterized by a larger proportion of unequal double cones compared with the ventral retina. Together, our results suggest that large opsin repertoires serve to optimize visual function under variable light environments by differential expression of opsin subsets with retinal location. Abstract : Using molecular and physiological data, the authors reveal the juvenile starry flounder retina is highly specialized with adaptations for demersal life history. These data suggest that large opsin repertoires serve to optimize visual function under variable light environments by differential expression of opsin subsets with retinal location.